Genomic epidemiology of invasive Group A Streptococcus infections in Argentina, 2023: high prevalence of emm1-global and detection of emm1 hypervirulent lineages - Lucía Cipolla; Ariel Gianecini; Tomas Poklepovich; Paula Etcheverry; Florencia Rocca; Mónica Prieto (Microbiology Spectrum)
ABSTRACT The aim of this study is to describe the genomic epidemiology of invasive Group A Streptococcus (iGAS) in Argentina during 2023. A total of 476 invasive GAS isolates were subtyped and analyzed by whole-genome sequencing. A high prevalence of the emm1-type strain was observed. Among the emm1 strains, two highly virulent international variants, emm1-UK and emm1-DK, were identified. Additionally, a local variant, called emm1-ST1319, was detected. This seminal study provides initial insights into the genomic landscape of iGAS, contributing to active surveillance to monitor emerging virulent emm1 lineages and cross-border transmission in South America.IMPORTANCEAmid the increase in invasive Streptococcus pyogenes infections in Argentina in 2023, the implementation of genomic analysis of isolates allowed us to detect at the national level the prevalence of the emm1 type and within the M1 type, emerging national and international hypervirulent lineages. These findings from our report shed light on the distribution of invasive Group A Streptococcus, laying the foundation for genomic surveillance of this pathogen.